ANALISIS RESEPSI NETIZEN DI MEDIA SOSIAL X ATAS PERNYATAAN AKTOR ABIDZAR DALAM FILM ADAPTASI A BUSINESS PROPOSAL - Hana Mauidunnajah; Rizki Fitrianti; Arfian Suryasuciramdhan; Eka Susilawati; April Laksana (Communication Science Department - Faculty of Social and Political Sciences, Universitas Satya Negara Indonesia (USNI), 2026)
In film promotion, actors are required to maintain their public image by paying attention to ethics and the words they use. This study examines netizens’ reception on social media X toward Abidzar’s statement during the promotion of the film adaptation A Business Proposal, using a qualitative method with a netnographic approach. The analysis focuses on netizen comments from four different menfess accounts, applying Stuart Hall’s reception theory consisting of dominant hegemonic, negotiated, and oppositional readings. The findings reveal diverse responses, with oppositional positions being the most dominant, reflected in harsh criticism and the emergence of Cancel culture as a form of digital social sanction. This study highlights social media X as an active arena of meaning negotiation, where audience reception is shaped by personal, social, and cultural experiences.